Diseño de un sistema automatizado para emergencias contra fuego y gas para el tanque esférico YT-7711 - Calvo-Torres, Raúl Ariel (Instituto Tecnológico de Costa Rica, 2013)
In the last 24 years, the national domestic demand for liquefied petroleum gas (LPG) shows a steady growth trend. To address this demand, RECOPE requires several spherical tanks to store, import, and draw off LPG in the refinery in Moín, from which the designated tank YT-7711 will be the first to be built. The YT-7711 tank must have an automated system for fire and gas emergency. This system has to be developed with the latest technology and safe control concepts. All processes involved must be developed in accordance with best engineering practices for this type of industry, whenever the case, based on international standards. The equipment and instruments used in this project such as programmable logic controllers, flame and gas detectors, electrically operated solenoid valves and other, have emerged as ideal tools for control, surveillance and system action against fire and gas emergency, creating a safer environment for the sphere YT-7711. The activation of the system should be automatic and if necessary manual activation, this can be remotely done via the supervisory control and data acquisition (SCADA) system or field devices that activate the system. The deactivation of the system, because of safety standard must be done manually, conducted by field operators trained to perform this function. There must be some means of audible and visual alarm that notify officials of an emergency situation.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2013.
Keywords: Alarmas; Fuego; Extinción de incendios; Válvulas de seguridad; Gas líquido; Petróleo